Institutional investors’ role in implementing book building: Views of market participants - Jas Bahadur Gurung; Lija Boro; Ramkrishna Chapagain (Investment Management & Financial Innovations)
The aim of this paper is to assess the views of market participants concerning the institutional investors’ role in implementing book-building pricing of IPOs as Nepal seeks to implement it. A total of 125 market participants were approached for data collection using a structured questionnaire that took a six-month period from January to June 2020. Descriptive and inferential statistics were employed to analyze the collected data. The study found that the role of institutional investors in the prevailing stock market is brutally meager because of the restrained regulatory provisions. Market participants opined that institutional investors play a vital role in developing the stock market and executing book building. Implementation of book building demands a rigorous amendment in the existing regulations that allow institutional investors to enter and play in the market. A precise classification and definition of the potential roles of institutional investors are essential so that the application of the building pricing mechanism could be expected to be more effective. Market participants believed that the active participation of institutional investors will help lure manufacturing and real sector companies, trading houses and hotels into the capital market for public offerings. Issue managers, portfolio managers, share registrars, and stockbrokers agree that the role of institutional investors is inevitable in implementing book-building pricing.